2021
DOI: 10.3389/fpsyg.2021.682154
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among Cancer Patients During COVID-19 Pandemic in the World: A Systematic Review

Abstract: Aim: Patients with malignancies, experience high rates of psychological distress. Fear of Corona-infection combined with the interruptions in some treatment programs might affect the psychological health of cancer patients. This review study was conducted to investigate the psychological distress among cancer patients during COVID-19 pandemic to offer system-adapted individual solutions.Materials and methods: To identify the psychological distress of cancer patients, a comprehensive search was carried out in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
72
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 67 publications
5
72
1
Order By: Relevance
“…Levels of anxiety and depression have been shown to be higher in head and neck cancer patients than other oncological populations at baseline [ 23 ]. The additional stressor of a delay in care during the pandemic may exacerbate emotions of fear, anxiety, and distress [ 23 , 28 , 29 ]. During the pandemic, psychological distress can impact a patient’s decision regarding their care and treatment.…”
Section: Psychosocial Assessment: Implications Of Delays In Carementioning
confidence: 99%
See 4 more Smart Citations
“…Levels of anxiety and depression have been shown to be higher in head and neck cancer patients than other oncological populations at baseline [ 23 ]. The additional stressor of a delay in care during the pandemic may exacerbate emotions of fear, anxiety, and distress [ 23 , 28 , 29 ]. During the pandemic, psychological distress can impact a patient’s decision regarding their care and treatment.…”
Section: Psychosocial Assessment: Implications Of Delays In Carementioning
confidence: 99%
“…During the pandemic, psychological distress can impact a patient’s decision regarding their care and treatment. The most common identified causes for psychological distress in cancer patients have been fear of contracting COVID-19, fear of disease progressions, interruption of oncology care, and immunocompromised status [ 29 ]. Some research has even suggested that anxiety related to COVID-19 may be so crippling for cancer patients that they may refuse treatment due to fear of infection [ 29 ].…”
Section: Psychosocial Assessment: Implications Of Delays In Carementioning
confidence: 99%
See 3 more Smart Citations